An exploratory study of how programming instructors illustrate variables and control flow - André L. Santos; Hugo Sousa (17th Koli Calling International Conference on Computing Education Research, Koli Calling 2017, 2017)
We present an exploratory study that investigated how programming instructors illustrate program execution, namely variable manipulation and control flow. The study involved tasks where instructors were asked to doodle illustrations of program execution in a sheet of paper for given Java methods with example input/output. We found eight illustration patterns, some of which relate to specific variable roles (Gatherer, Stepper for array indexing, Most Wanted Holder). By analyzing existing pedagogical animation and debugging tools, we conclude that their visualizations do not have a broad representation of the aspects evidenced by the illustration patterns of instructors, hinting that human illustrations tend to be considerably richer.